(untitled) (Global Journal of Management and Business Research, 2012)
The study was designed to investigate the acquisition of entrepreneurial skills via the provision and utilization of facilities and equipment in Lagos State Public Junior Secondary Schools. Three hypotheses were formulated and tested at 0.05 level of significance. Population for the study included the 288 public Junior Secondary Schools in Lagos State out of which 60 were randomly selected for the study. A questionnaire was developed, validated and used to collect data for the study. Data collected were analyzed through the use of Pearson Product- Moment Correlation Coefficient Analysis. The findings reveal that, from the provision of facilities, students were able to acquire entrepreneurial skills moderately; also that the more the students utilize provided facilities, the more they acquire entrepreneurial skills and finally, that as the facilities are provided so are they utilized by the students.